1992
DOI: 10.1126/science.1281928
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of Nitric Oxide and Its Redox-Activated Forms

Abstract: Nitric oxide (NO.), a potentially toxic molecule, has been implicated in a wide range of biological functions. Details of its biochemistry, however, remain poorly understood. The broader chemistry of nitrogen monoxide (NO) involves a redox array of species with distinctive properties and reactivities: NO+ (nitrosonium), NO., and NO- (nitroxyl anion). The integration of this chemistry with current perspectives of NO biology illuminates many aspects of NO biochemistry, including the enzymatic mechanism of synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
1,459
2
50

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,593 publications
(1,535 citation statements)
references
References 78 publications
24
1,459
2
50
Order By: Relevance
“…This increased pool of extracellular NO was contradictory to the lower radiosensitising activity, which again confirms the lack of correlation between NO production and radiosensitising activity for bioreductive NO donors. Endogenously formed GSNO is conceivably the major adduct of natural thiols, with nitrosonium cation accumulated in cells after exposure to NO (Ignarro et al, 1981;Stamler et al, 1992;Clancy et al, 1994). As such, it may also be involved in the trapping and storing of SNP-derived NO adducts in hypoxic cells, thereby supporting delayed radiosensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…This increased pool of extracellular NO was contradictory to the lower radiosensitising activity, which again confirms the lack of correlation between NO production and radiosensitising activity for bioreductive NO donors. Endogenously formed GSNO is conceivably the major adduct of natural thiols, with nitrosonium cation accumulated in cells after exposure to NO (Ignarro et al, 1981;Stamler et al, 1992;Clancy et al, 1994). As such, it may also be involved in the trapping and storing of SNP-derived NO adducts in hypoxic cells, thereby supporting delayed radiosensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein. 19,20,22,55 Alternatively, S-nitrosylation may possibly produce a nitroxyl disulfide, in which the NO group is shared by close cysteine thiols.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…Given the rich chemistry (for review, see ref. 60) and biochemistry of NO, and the variety of cell types that produce this radical, it is not surprising that NO influences a wide range of physiologic processes. These are listed in Table 2.…”
Section: Biochemical Properties Of Nitric Oxidementioning
confidence: 99%